Education about Medical Vocabulary Using English for SMP Baiturrahim Jambi - Warahmah, Mawaddah; Hasmar, Wanti; Sari, Indah Permata (Jurnal Ilmiah Pengabdian Masyarakat Bidang Kesehatan (Abdigermas), 2023)
This activity aims to educate medical vocabulary skills in English for junior high school students to educate them in health education. The skills needed by students will be used as the basis for the preparation of teaching materials in English subjects intended and recommended for SMP Baiturrahim students. This community service took place at SMP Baiturrahim. This educational method uses the approach of providing materials and leaflets to students and teachers at SMP Baiturrahim in Jambi. SMP Baiturrahim which is located at Jalan H. Syamsoe Bachroen No. 32 RT. 04, Selamat, Kec. Danau Sipin, Jambi City, Jambi Province with 24 teachers, 53 male students, and 32 female students. Based on the education results, the Vocabulary Self-Collection Strategy (VSS) was successfully applied in English subjects with a good category at the beginning of educational activities and a very good category during the implementation of education at SMP Baiturrahim. In educational activities, the learning steps that have not reached the success criteria are strategy and environment. While the steps that have reached the success criteria are learning resources and students. In the next stage, there was an improvement in the learning process so that all learning steps had improved and reached the success criteria.